Al-Mar’ah fi al-Qur’ân ‘Inda Ibn ‘Asyûr fi Tafsîrih (Dirâsah ad-Dilâlah al-Qur’âniyyah) - Ali Mahfuz Munawar; Dyah Nurul Azizah (Studia Quranika, 2017)
There are various studies about al-Mar’ah in the Qur’an, also the term that is used for the context of mar’ah, including imra’ah and nisâ’. With the semantic approach, Ibnu Asyur tries to study this theme is according to imra’ah and an-nisâ’. This paper found that term imra’ah has a more specific meaning than "an-nisa", also devoted to the two writing styles, with ta' ta'nîts (امرأت ) which is more oriented to have the meaning "wife", and the writing with ta 'marbuthah (امرأة ) is used for 4 types of mar'ah they are barren women, old women, widow, and unmarried women. While for term an-nisâ’ is a plural form of imra’ah which is dissaproved from the ashlu al-kalimah, on the meaning women or adult female.